Petrogenetic of Igneous Complex of Ilota Nanasi Gold Deposit, Gunung Pani, Gorontalo, Indonesia - Rompo, Iryanto; Ismail, Fajar; Santoso, STJ Budi; Rosana, Mega Fatimah; Yuningsih, Euis Tintin (UIR PRESS, 2023)
Ilota Nanasi Au-Ag deposit located in the western flank of the Gn. Baganite, a part rhyodacite dome in Gn. Pani district, Gorontalo Province, where the extensive exploration programs were carried out by PT Gorontalo Sejahtera Mining (a subsidiary of PT J Resources Nusantara) from 2012 – 2020. As the result, a total of 72.7 Mt @ 0.98 g/t Au and 0.85 g/t Ag (2.3 Moz Au and 2.6 Moz Ag) mineral resource was delineated in 2019. This paper mainly aimed to the petrogenesis association of granitoid basement and rhyodacite unit as the host rock in the Ilota Nanasi gold deposit. The geology of Ilota Nanasi is overlain by Late Miocene granodiorite, andesite and diorite basement, Pliocene volcanic complex predominantly dacite – rhyodacite, tuff, breccia, and quaternary deposit as alluvial and surface breccia. Hydrothermal alteration and gold – silver mineralization centered in the porphyritic rhyodacite host rocks where the intense silicification forming a zone around the hydrothermal crackle breccia unit and/or high-density quartz vein, veinlets and stockworks. Mineralization in Ilota Nanasi is interpreted as a low sulfidation epithermal system dominated by a large volume of hydrothermal crackle breccia, intense quartz veining, veinlets, and high-density fracturing. A combined analytical result of petrography and whole-rock geochemistry has been used to assess the petrogenetic association of the rhyodacite and granitoid basement in the Ilota Nanasi. The result of the AFM diagram plot shows sample trends in calc-alkaline magma field. In contrast, the SiO2 – K2O plot distributed in two trends: the older unit was associated with high-K calc-alkaline and the shoshonite series for the younger unit. The changing of magma series is considered as product of crystallization differentiation of evolved parental magma or derived from the melting of mantle material after the mantle or lower crustal was metasomatized during a former episode of subduction.